Artificial light at night usage patterns and their implications for human wellbeing, ecological balance, and astronomical visibility within the nighttime ecosystem of Brenton-on-Sea, Knysna - Louw, Ilonka; Mearns, Kevin; Makoni, Logistic (Edelweiss Applied Science and Technology, 2025)
The purpose of this research was to investigate the usage patterns and implications of artificial light at night (ALAN) and its effects on ecological integrity, human health, and astronomical visibility within the conservation-based coastal town of Brenton-on-Sea, Knysna. In this quantitative study, survey data from [n = 49] households were obtained regarding residents’ perceptions of artificial lighting and their lighting behaviors. The data reveal a dominant use of functional outdoor lighting, particularly white light, primarily driven by visibility and security needs. The findings also indicate limited awareness of ALAN’s broader ecological and health impacts. Despite this, residents demonstrated a high willingness to learn more about ALAN and how to mitigate it through responsible lighting practices. The results highlight a significant disconnect between lighting behavior and ecological responsibility, providing evidence-based insights into the challenges and opportunities for sustainable lighting in similar conservation-sensitive regions. This localized insight into ALAN’s real-world impacts offers a critical foundation for modeling context-specific, responsible, and sustainable lighting strategies that can be adapted across similar conservation-oriented communities globally.